A efetividade da avaliação e intervenção dos processos de compreensão de leitura segundo o DislexiaBrasil - Aline D'Avila Barbosa (2016)
This dissertation aims to analyze the effectiveness of topical "informal assessment of reading comprehension by the teacher in the classroom" and "understanding of teaching practices" contained in a course "Online Learning", referred to as DislexiaBrasil (DB). The course is intended to free training education students and the elementary school teachers 1 (EF1) on learning to read, focusing on identifying and teaching children with learning difficulties in this skill. two studies with teachers were developed (divided into two groups: experimental (EG) and control (CG)) and students of the 2nd and 3rd year of the four schools of the municipal public of the city of Santa Luzia (metropolitan region of Belo Horizonte) with students of the teachers of each group forming the GE and GC children. Studies 1 and 2 are intended, respectively, answer the following questions about these DB topics: 1) the content included in the first topic enable teachers to conduct an effective assessment of reading comprehension? and 2) the second topic content offer effective ways and means to remedy reading comprehension problems? To answer the first question, the first study was divided into three phases. Phase 1.1 (Screening) aimed to exclude from the initial sample of 165 students who did not meet the established criteria in reading two tests of word recognition. After applying the exclusion criteria (70% accuracy in word reading and 60% in pseudoword reading), 120 students (57 GE and 63 GC) comprised the sample of Phase 1.3 (Assessment of reading comprehension skills) . In Phase 1.2 (Training of teachers), teachers were asked to create activities and objective criteria that would enable them to assess, in Phase 1.3 (AVAInformal) reading comprehension of the students in order to identify those with difficulties in this skill. While the teachers of GE (n = 3) received training on how to assess reading comprehension (according to DB), no information and follow-up on how to perform such a task were offered to teachers GC (n = 3). The product of this phase of the study - the type of activity selected and the criteria developed for evaluation - was the same for both groups, "reading a text (which varied from teacher to teacher), then ten questions its contents. " This result was due to the fact that teachers of GE, as the GC, have done what they knew and were using the standard model laid down by the city. In Phase 1.3, the reading comprehension skills were assessed in two ways: AVAInformal (conducted by teachers and performed with all children in the classroom, through the text (and questions about it) chosen by each teacher in Phase 1.2.) and AVAFormal (conducted by graduate student, but with only 120 students selected in Phase 1.1, through formal instruments). The results of this phase indicated that in AVAInformal there was a high percentage of students with performance "weak and Good" in GE and "excellent" in the GC, contrasting with the AVAFormal results in 41.9% and 15.1% of them ( respectively the experimental and control groups, with most of the 3rd year) showed difficulties in reading comprehension in formal instruments. Together, the results in study 1 revealed: 1) the high percentage of children 2 and 3 years not decode still well nor have accuracy and fluency in reading; 2) the large deficit in the training of literacy teachers; and 3) the difficulty of conducting research in schools due to administrative and institutional issues of school and the interest and availability of the teacher himself Finally, in this study, due to the aforementioned limitations, it was not possible to verify the effectiveness of the topic "Evaluation informal reading comprehension by the teacher in the classroom, "available in DislexiaBrasil.